Robust real rate rules - Tom D. Holden (Deutsche Bundesbank, 2022)
Central banks wish to avoid self-fulfilling fluctuations. Monetary rules with a unit response to real rates achieve this under the weakest possible assumptions about the behaviour of households and firms. They are robust to household heterogeneity, hand-to-mouth consumers, non-rational household/firm expectations, active fiscal policy, missing transversality conditions and to any form of intertemporal or nominal-real links. They are easy to employ in practice, using inflation protected bonds to infer real rates. With a time-varying inflation target, they can implement arbitrary inflation dynamics, including optimal policy. They work thanks to the key role played by the Fisher equation in monetary transmission.
Keywords: E52; E43; E31; 330; robust monetary rules; determinacy; Taylor principle; inflation dynamics; monetary transmission mechanism